Amino acids composition and antioxidant activity of selected mushrooms from Bosnia and Herzegovina - Salihović, Mirsada; Šapčanin, Aida; Pehlić, Ekrem; Uzunović, Alija; Špirtović-Halilović, Selma; Huremović, Melita (2019)
Many studies highlight the health benefits of mushrooms, which are consequently becoming more and more interesting for researchers. The content of amino acids (AA), total phenolic content (TPC), and antioxidative activity (AAc) were determined in wild as well as cultivated mushrooms. The AA included: L-tryptophan (Trp), L-arginine (Arg), L-cysteine (Cys), L-methionine (Met), L-alanine (Ala), L-phenylalanine (Phe), L-lysine (Lys), L-valine (Val), L-glycine (Gly), and L-leucine (Leu). The wild mushrooms: Lactarius piperatus, Amanita caesarea, Lactarius deliciosus, Lycoperdon pyriforme, Macrolepiota procera, and cultivated mushrooms: Agaricus bisporus, Boletus aestivalis, Cantharellus cibarius, Pleurotus ostreatus, and Agaricus bisporus var. avellaneus were investigated in this study. The AA was determined by HPTLC method and quantified with a Camag TLC scanner and WINCAT software by scanning the plates at 540 nm. The TPC was spectrophotometrically estimated as gallic acid equivalents/g of fresh weight according to Folin-Ciocalteu’s method. The radical scavenging activity (RSA) of mushroom extracts was determined by DPPH assay. The highest content of Ala, Gly, Phe, Lys, Val, and Leu was found in Pleurotus ostreatus. The total phenolic content (mg GAE/g) in investigated mushrooms ranged from 1.90 to 35.56, and the % RSA ranged from 43.88 to 90.17. This study promotes the consumption of food rich in bioactive compounds, mushrooms being among such food. Further research on mushrooms from Bosnia and Herzegovina and their benefits in the overall maintenance of human health and protection from age-related diseases is necessary.
Mnoga istraživanja ističu zdravstvene prednosti gljiva, koje stoga postaju sve zanimljivije za konzumente i istraživače. Sadržaj aminokiselina (AA) i ukupnih fenola (TPC) te antioksidacijska aktivnost (AAc) utvrđeni su u samoniklim i kultiviranim gljivama. Analizirane AA su: L-triptofan (Trp), L-arginin (Arg), L-cistein (Cys), L-metionin (Met), L-alanin (Ala), L-fenilalanin (Phe), L-lizin (Lys), L-valin (Val), L-glicin (Gly) i L-leucin (Leu). Od samoniklih gljiva analizirane su: Lactarius piperatus, Amanita caesarea, Lactarius deliciosus, Lycoperdon pyriforme, Macrolepiota procera, a od kultiviranih gljiva ispitivane su: Agaricus bisporus, Boletus aestivalis, Cantharellus cibarius, Pleurotus ostreatus i Agaricus bisporus var. avellaneus. Određivanje AA provedeno je metodom HPTLC, a kvantifikacija je provedena skenerom Camag TLC i softverom WINCAT skeniranjem ploča na 540 nm. TPC je spektrofotometrijski određen kao ekvivalent galne kiseline/g svježe mase metodom Folin-Ciocalteu. Aktivnost hvatanja radikala (RSA) ekstrakata gljiva određena je DPPH testom. Najveći sadržaj Ala, Gly, Phe, Lys, Val i Leu nađen je u Pleurotus ostreatus. Sadržaj ukupnih fenola (mg GAE/g) u ispitivanim gljivama kretao se u rasponu od 1,90 do 35,56, a % RSA u rasponu od 43,88 do 90,17. Ovo istraživanje promovira konzumiranje hrane bogate bioaktivnim spojevima, kojima pripadaju i gljive. Stoga je nužno nastaviti istraživanje gljiva s područja Bosne i Hercegovine radi utvrđivanja njihove dobrobiti za cjelokupno održavanje zdravlja ljudi i zaštite od oboljenja povezanih sa starenjem.
Bibliografija: 28 jed.
Summary ; Sažetak.
Keywords: Gljive -- Aminokiseline -- Antioksidacijska aktivnost; Bosna i Hercegovina